Сhoosing the best type neural network jet contour diagnostics engines - Якушенко, О.С. (Proceedings of National Aviation University (archive), 2006)
In the paper the choice problems of neurons type for neural network is considered. The neurons types has to be , optimal from the point of work stability, training speed and quality of gas turbine engine technical condition class recognition by work process parameters. Results of researches are given.